Impact of Group 10 Metals on the Solvent‐Induced Disproportionation of o‐Semiquinonato Complexes. Issue 35 (21st May 2019) - Yamada, Shota; Matsumoto, Takeshi; Chang, Ho‐Chol
Abstract: The oxidation of [M II (3, 5‐DTBCat)(DTBbpy)] (M=Ni ([Ni] ), Pd ([Pd] ), and Pt ([Pt] ); 3, 5‐DTBCat=3, 5‐di‐ tert ‐butylcatecholato; DTBbpy=4, 4′‐di‐ tert ‐butyl‐2, 2′‐bipyridine) afforded the dimeric {[Ni II (3, 5‐DTBSQ)(DTBbpy)](PF6 )}2 ({[Ni](PF6 )}2 ; 3, 5‐DTBSQ=3, 5‐di‐ tert ‐butylsemiquinonato) and monomeric semiquinonato (SQ) complexes [M II (3, 5‐DTBSQ)(DTBbpy)](PF6 ) (M=Pd ([Pd](PF6 ) ) and Pt ([Pt](PF6 ) )). The negative solvatochromic properties of the SQ complexes allowed us to estimate the relative order of their dipole moments: [Pd](PF6 ) >[Pt](PF6 ) >{[Ni](PF6 )}2 . The complexes [Pd](PF6 ) and [Pt](PF6 ) adopt monomeric structures and are stable in CH2 Cl2 and toluene, whereas they gradually disproportionate at room temperature to [M] and 3, 5‐di‐ tert ‐butylbenzoquinone (3, 5‐DTBBQ) in polar solvents such as THF, MeOH, EtOH, DMF, or DMSO. The results of spectroscopic studies suggested that the oxidized nickel complex adopts a monomeric structure ([Ni](PF6 ) ) in CH2 Cl2, but a dimeric structure ({[Ni](PF6 )}2 ) in the other investigated solvents. In polar solvents, {[Ni](PF6 )}2 may disproportionate to [Ni] and 3, 5‐DTBBQ at 323 K, thereby demonstrating a significant solvent‐ and metal‐dependence in temperature. The relative activities of {[Ni](PF6 )}2 and [M](PF6 ) toward disproportionation are related to the electrochemically estimated K dis values in CH2 Cl2 and DMF. The present work demonstrates that solvent polarity and the dipole moments of the SQ complexes promote disproportionation, which can be controlled by a judicious choice of the metal ion, solvent, and temperature. Abstract : High dependency ! The results of this study demonstrate the metal‐, temperature‐, and solvent‐dependent disproportionation behavior of Group 10 metal (Ni, Pd, and Pt) complexes with semiquinonato radical ligands (see figure). It can be concluded that the stability and degree of disproportionation of the complexes can be controlled by a judicious choice of the metal ion, solvent, and temperature.